Nonylphenol promotes epithelial-mesenchymal transition in colorectal cancer cells by upregulating miR-151a-3p - Biao Wang; Nianjie Zhang; Lin Dai; Yuanwei Zhang; Shuo Yin; Xuefeng Yang (Discover Oncology)
Abstract Nonylphenol (NP) is a common environmental contaminant and endocrine disruptor. Our previous research demonstrated that NP could promote the proliferation and epithelial-mesenchymal transition (EMT) of colorectal cancer (CRC) cells; however, the specific mechanism remains unclear. miRNA sequencing revealed that NP upregulated the expression levels of microRNA(miR)-151a-3p in CRC. Analysis of The Cancer Genome Atlas (TCGA) data revealed increased expression levels of miR-151a-3p in CRC tissues. The present experiments showed that NP could activate the WNT/β-catenin signaling pathway, and promoted the migration and invasion of CRC cells by increasing the expression levels of miR-151a-3p. Through bioinformatics analysis and dual-luciferase reporter assays, Fyn-related kinase (FRK) was identified as a target gene of miR-151a-3p. Knockdown of FRK promoted NP-induced EMT in CRC cells and activated the WNT/β-catenin signaling pathway, while overexpression had the opposite effect. In summary, the present study demonstrated that NP could inhibit FRK expression via miR-151a-3p, activate the WNT/β-catenin signaling pathway, and promote EMT in CRC cells.